2001
DOI: 10.1021/bm000121r
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide−Polynucleotide Complexes. 2. Complementary Polynucleotide Mimic Behavior of the Natural Polysaccharide Schizophyllan in the Macromolecular Complex with Single-Stranded RNA and DNA

Abstract: Schizophyllan is an extracellular polysaccharide consisting of a beta-1,3-D-glucan main chain and exists as a triple helix in water and as a single chain in dimethyl sulfoxide (DMSO). When the single chain of schizophyllan (s-SPG) was mixed with poly(C), poly(A), poly(dA), or poly(dT), they form a macromolecular complex. On the other hand, poly(G), poly(U), poly(I), poly(dG), and poly(dC) do not. This nucleotide specificity evidences that the hydrogen bonds are essential to form the complex, because the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
131
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 49 publications
12
131
1
Order By: Relevance
“…SPG forms a stoichiometric complex with particular homo nucleotides such as poly(C) or poly(dA) via combination of hydrogen bonding and hydrophobic interactions (9)(10)(11). On the basis of our previous studies, we attached dA 40 to the AS-ODN to enable complex formation with SPG and thus efficient gene silencing (13,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPG forms a stoichiometric complex with particular homo nucleotides such as poly(C) or poly(dA) via combination of hydrogen bonding and hydrophobic interactions (9)(10)(11). On the basis of our previous studies, we attached dA 40 to the AS-ODN to enable complex formation with SPG and thus efficient gene silencing (13,14).…”
Section: Resultsmentioning
confidence: 99%
“…1) has a main chain comprising β-(1➝3)-D-glucan and one β-(1➝6)-D-glycosyl side chain that links to the main chain at every three glucose residues (8). We found that SPG forms a complex with single-stranded homo-polynucleotides and examined the fundamental properties of this complex (9)(10)(11). We recently started to apply this complex to therapeutic oligonucleotide delivery, including CpG DNA (12) and siRNA (13).…”
Section: Introductionmentioning
confidence: 99%
“…The molar ratio of SPG repeating unit to ODN base number was always fixed at 1.5:1.0, which is an excess of SPG over the stoichiometric number. 13 The detail method of the complexation of ODN with SPG was described elsewhere. 12 Telomerase Assays.…”
Section: Spgmentioning
confidence: 99%
“…We have found that a natural polysaccharide, called schizophyllan (SPG), can complex with single-stranded homo polynucleotides, without using cation/anion interactions. 12,13 Here, SPG consists of -(1!3)-D-glucan main chain and one -…”
mentioning
confidence: 99%
See 1 more Smart Citation